1999
DOI: 10.1152/ajpregu.1999.277.6.r1741
|View full text |Cite
|
Sign up to set email alerts
|

PGE2suppresses mitogen-induced Ca2+mobilization in T cells

Abstract: PGE2-mediated suppression of T cell proliferation during sepsis could result from altered Ca2+ signaling. The present study evaluated the effects of PGE2 on Ca2+ release from intracellular stores and its influx through the plasma membrane in splenic T cells from Sprague-Dawley rats. Intracellular Ca2+ concentration ([Ca2+]i) responses in individual T cells were assessed using the Ca2+ imaging technique, and the release of Ca2+ from intracellular stores and Ca2+ influx were spectrofluorometrically quantified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Thus the suppression in p38 and ERK1/2 is likely to play a major role in Cort-mediated suppression of T cell proliferations and IL-2 production after a combined insult of EtOH intoxication and burn injury. Previous studies from our laboratory and others have shown that T cell dysfunction during burn and sepsis is accompanied with alterations in P59 fyn kinase activity, PKC, and Ca 2ϩ signaling (7,8,9,12,25). Because the activation of P59 fyn and Ca 2ϩ signaling precedes p38 and ERK1/2 activation, alterations in either of these pathways may potentially contribute to a suppression of p38 and ERK1/2 in T cells in EtOH and burn injury.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Thus the suppression in p38 and ERK1/2 is likely to play a major role in Cort-mediated suppression of T cell proliferations and IL-2 production after a combined insult of EtOH intoxication and burn injury. Previous studies from our laboratory and others have shown that T cell dysfunction during burn and sepsis is accompanied with alterations in P59 fyn kinase activity, PKC, and Ca 2ϩ signaling (7,8,9,12,25). Because the activation of P59 fyn and Ca 2ϩ signaling precedes p38 and ERK1/2 activation, alterations in either of these pathways may potentially contribute to a suppression of p38 and ERK1/2 in T cells in EtOH and burn injury.…”
Section: Discussionmentioning
confidence: 87%
“…fyn , which phosphorylate Zap-70 (7,9,12,17,26). ZAP-70 then phosphorylates phospholipase C-␥ (PLC-␥) to hydrolyze phosphatidylinositol 4,5-bisphosphate into D-myoinositol 1,4,5-trisphosphate [Ins(1,4,5)P 3 ] and diacylglycerol (DAG).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused on the direct effect of PGE 2 in mediating suppression of lymphocyte proliferation, highlighting the role of calcium-dependent mechanisms (29,30). In the current study we first investigated whether exogenous PGE 2 was able to augment the suppressive activity of CD4 ϩ CD25 ϩ T reg cells.…”
Section: Pge 2 Enhances Cd4mentioning
confidence: 99%
“…18,19). PGE 2 has been shown to inhibit T-cell proliferation by altering polyamine synthesis (20), inhibiting intracellular calcium release (21), and inhibiting p59 protein tyrosine kinase (22). PGE 2 profoundly inhibited IFN-g and IL-2 production (23) while enhancing IL-4 and IL-10 production (24), thereby promoting a Th2 response over a Th1 antitumor response.…”
mentioning
confidence: 99%